Divng behavior of emperor penguins nurturing chicks at Coulman Island, Antarctica - Kooyman, G. L.; Kooyman, T. G. (Cooper Ornithological Society, 1995)
At the largest known Emperor Penguin colony, we determined general features of Emperor Penguin foraging commutes. The time selected for the study was one month before fledging, when maximum growth of the chicks occurs. Time/depth recorders were attached and retrieved from five adults as they departed from and returned to the colony. Nearly 16,000 dives were logged, of which 7,562 were estimated to be for foraging. Duration of the commutes averaged 14.9 days during which the birds averaged a total of 3,188 dives or 2 13 dives per day. Dives ~200 m occurred at any time through the 24 hr cycle, and dives >400 m were restricted to 05:OO to 19:OO hr. The deepest dive was 534 m and the longest was 15.8 min to a depth ~50 m. The modal depth of foraging dives was between 21 to 40 m, and the modal duration was between 4 and 5 min. Descent and ascent depth change rates were influenced by the maximum depth of the dive, but usually for dives > 100 m the rates fell between 1.0 to 2.0 m set’. The rates never exceeded 2.5 m seccl. Bottom time fraction was 0.22 to 0.28 of total dive time, for dives > 100 m. Although few in number, occurrence of dives > 450 m appeared consistently during the commute of every bird and suggests some important but unknown function. Because dives >400 m occurred only during high sun periods, it is proposed that such dives may not occur during the austral winter niaht. From behavioral data it anoears that the aerobic dive limit (ADLl of about 8 min is nearly twice the calculated ADL.-if this is so, then < 5% of all dives exceed the ADL. Diving efficiency derived from diving and surface time in relation to bottom time declines by 50°h between 100 m and 300 m dives.